Pelayanan Pastoral Terhadap Tuan X Pecandu Narkoba Di Tarutung Kabupaten Tapanuli Utara Tahun 2023 (Jurnal Pendidikan Agama dan Teologi, 2023)
This research is motivated by the fact that in the rehabilitation process, most drug addict victims (clients) are unable to solve their own problems, so assistance is really needed, namely pastoral care. The research method used is qualitative research. In the research, the researcher describes and analyzes Pastoral Care for Mr. The subjects in the research (people who can provide information or information in the research) are: drug addicts as residents (prisoners/inmates of the Tarutung Class II B State Detention Center) and counselors (someone who has expertise in the field of pastoral care). The analysis technique uses a descriptive method which is carried out by collecting all existing results. The results of the research concluded that the counselor's efforts in providing assistance (helping and guiding) for drug addict victims in the Tarutung class II B State Detention Center were going well through Individual Counseling: Counseling as a motivator, the counselor's efforts in motivating residents, fostering confidence in residents. The counselor as a counselor facilitator in this case helps the resident by providing the facilities the resident needs in life. The counselor acts as a mediator, so that this is done by means of the counselor as a mediator between the resident and the resident's family.